Waithood: Tren Penundaan Pernikahan pada Perempuan di Sulawesi Selatan - Rani Wulandari (Emik, 2023)
Nowadays there are many people around the world who prefer to delay their marriage. Delaying of marriage has become a trend resecently and it increases globally. While most of literatures on waithood dealing with social life change, this article focuses on the trend of waithood among women. Using qualitative approach, this study was conducted in South between August and November 2022. The study involved 10 participants whose age range between 30 to 34 years old. While they also vary on the basis of their job, namely teacher, nurse, civil worker, private sector worker, banker, entrepreneur, and stewardess, two of them are unemployed. The results of this study indicate that there are several reasons why women choose to delay their marriage, namely aiming to focus on their careers, are not financial ready, are not mentally ready, intending to focus on family, be selective in choosing a partner, and intending to live independently. Women who choose to waithood play a role as agents who can enjoy their own freedom, may focus to chase their dreams, and to enjoy life. It is argued in this article that despite the fact that married status is still idealized, waithood has become more common and more socially acceptable.